Bioaccumulation of rare earth element by water lettuce (Pistia stratiotes) - Muhd N.Muhammad, Nazreen; A. N., Amalina; Omar, Muhammad Nor (Oriental Scientific Publishing Company, 2017)
Processing of rare earth elements produces environmental wastewater pollution containing toxic contaminants. However, these pollutants could be monitored through bioaccumulation using aquatic plant, Pistia stratiotes. Thus, the present research aims to determine the effectiveness of P. stratiotes in the bioaccumulation of rare earth metals through phytoremediation. The study was carried out by subjecting the plant to 5 levels of lanthanum chloride treatment for 7 days. The plant samples (root and leaf sections) were digested prior to metal accumulation analysis using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The results from the analysis showed that lanthanum accumulated in both the root and leaf sections of P. stratiotes. The highest concentration of lanthanum was found in the root section (0.272 μg kg ) on the 2 day compared to the leaf section (0.0124 μg kg ) on the 6 day, when both parts were treated with 1.0 ppm. The study indicates that this aquatic plant can be used to remediate environmental wastewater from REE contamination because of its bioaccumulation capability.